Using AHP BOCR analysis for experiential business education and prioritisation of international opportunities. (2016) - Mu, Enrique
This article reports the use of the analytic hierarchy process (AHP) to teach BOCR, an important managerial skill, to graduate management students, using the principles of experiential learning and working on the prioritisation of actual university international cooperation projects in a liberal arts university. The University-Uganda initiatives propose overseas cooperation between the university, Bright Kids Uganda, and project to end human trafficking Uganda. Three graduate teams utilised the AHP methodology to evaluate and prioritise each of the proposed initiatives from the three different perspectives of the schools of nursing, education, and psychology. The purpose of this article is two-fold: first, to report on this educational experience, and suggest best practices and lessons learned and second, to report on the BOCR results which will undoubtedly be useful for any higher-education institution considering overseas cooperation initiatives.